Associations between motivational factors and burnout syndrome among elite skiers - Wu, X.; Cai, Y.; Abidin, N. E. Z.; Jaladin, R. A. M. (BMC Psychology, 2023)
The present research investigated the association between a series of motivational factors and burnout syndrome among elite skiers at the contextual level within the Hierarchical Model of Intrinsic and Extrinsic Motivation (HMIEM). There are 352 subjects (258 males, 94 females, aged 18 to 25 years) across five skiing events from three sport universities in this study. Four psychological scales related to motivational factors and burnout syndrome were completed by subjects. Overall, the result showed that a task-involving climate had a positive relationship with basic psychological needs, eliciting a positive pathway to autonomous motivation, and thus negatively affecting burnout syndromes. On the contrary, an ego-involving climate had a negative relationship with basic psychological needs, then positively affecting burnout syndrome through amotivation. The results underscore the intricate associations between a variety of motivational factors and athletes` burnout syndrome, supporting the need to incorporate burnout syndrome elements into the outcomes of HMIEM sequence.